A comparative study of nematic liquid crystals doped with harvested and non-harvested ferroelectric nanoparticles: phase transitions and dielectric properties. Issue 56 (14th July 2017) - Lin, Y.; Daoudi, A.; Dubois, F.; Blach, J.-F.; Henninot, J.-F.; Kurochkin, O.; Grabar, A.; Segovia-Mera, A.; Legrand, C.; Douali, R.
Abstract : Broadband dielectric spectroscopy is used to determine the dielectric properties and phase transitions of the 4- n -octyl-4′-cyanobiphenyl liquid crystal (8CB) doped with harvested and non-harvested ferroelectric nanoparticles. Abstract : Harvested and non-harvested tin thiohypodiphosphate (Sn2 P2 S6 ) ferroelectric nanoparticles are used to dope the 4- n -octyl-4′-cyanobiphenyl liquid crystal (8CB). Due to their higher average spontaneous polarization, the harvested nanoparticles have stronger interactions with the liquid crystal molecules which leads to a higher order parameter as demonstrated by the increase in phase transition temperatures. This is confirmed by the results of dielectric characterization. In the homeotropic orientation, the increase in the order parameter leads to a higher dielectric permittivity. In the planar orientation, the coupling between the spontaneous polarization of the nanoparticles and the order parameter induces a slight reorientation of the liquid crystal director from the initial planar orientation, leading to an increase in the dielectric permittivity. This effect is more important for the liquid crystal doped with harvested nanoparticles.